Friedman's nobel lecture and the Phillips curve myth. - Forder, J (Cambridge University Press, 2010)
In his Nobel lecture, Friedman built on his earlier argument for a “natural rate of unemployment” by painting a picture of an economics profession which, as a result of foolish mistakes, had accepted the Phillips curve as offering a lasting trade-off between inflation and unemployment, and was thereby led to advocate a policy of inflation. It is argued here that, in fact, the orthodox economists of the time often did not accept Phillips’ analysis; almost no one made the mistakes in question; and very few advocated inflation on bases vulnerable to Friedman’s theoretical criticisms. The Phillips curve was put to various uses, but advocating inflation was hardly amongst them. It is suggested that one lasting result of the uncritical acceptance of Friedman’s history is to limit what appears to be within the reasonable range of views about macroeconomic policy.